Finance and Development, September 2003. (Finance and Development; Finance and Development, 2003)
This paper highlights that the Washington Consensus helped fill the need for an economic policy framework following the discrediting of central planning and import-substitution trade strategies. Latin American governments championed the Consensus in the early 1990s, and the policy agenda delivered some of the things it was supposed to-healthier budgets, lower inflation, lower external debt ratios, and economic growth. But unemployment rose in many countries and poverty remained widespread, while the emphasis on market openness made states vulnerable to the side effects of globalization.